DESIGNING EDUCATIONAL GAME “MATH MAZE” IN MATHEMATICS FOR GRADE 10th USING UNITY 3D - Melvin Nicholas Armansyah; Deli Deli (Universitas Internasional Batam, 2022)
Mathematics is a basic science that is used in everyday life, but so many children find it difficult to understand it at school. Children tend to like playing games rather than learning because games are very exciting and competitive, like wanting to have the highest score from other children. Game addiction is very dangerous, children tend to get emotional easily if they lose while playing games. However, if educational games are designed in such a way that children can play and learn in peace, it is very helpful. In this study, the author designed an educational game called